Visfatin Induces Inflammation and Insulin Resistance via the NF-κB and STAT3 Signaling Pathways in Hepatocytes - Yu Jung Heo; Sung-E Choi; Ja Young Jeon; Seung Jin Han; Dae Jung Kim; Yup Kang; Kwan Woo Lee; Hae Jin Kim (Journal of Diabetes Research)
Background. It has been suggested that visfatin, which is an adipocytokine, exhibits proinflammatory properties and is associated with insulin resistance. Insulin resistance and inflammation are the principal pathogeneses of nonalcoholic fatty liver disease (NAFLD), but the relationship, if any, between visfatin and NAFLD remains unclear. Here, we evaluated the effects of visfatin on hepatic inflammation and insulin resistance in HepG2 cells and examined the molecular mechanisms involved. Methods. After treatment with visfatin, the inflammatory cytokines IL-6, TNF-α, and IL-1β were assessed by real-time polymerase chain reaction (RT-PCR) and immunocytochemical staining in HepG2 cells. To investigate the effects of visfatin on insulin resistance, we evaluated insulin-signaling pathways, such as IR, IRS-1, GSK, and AKT using immunoblotting. We assessed the intracellular signaling molecules including STAT3, NF-κB, IKK, p38, JNK, and ERK by western blotting. We treated HepG2 cells with both visfatin and either AG490 (a JAK2 inhibitor) or Bay 7082 (an NF-κB inhibitor); we examined proinflammatory cytokine mRNA levels using RT-PCR and insulin signaling using western blotting. Results. In HepG2 cells, visfatin significantly increased the levels of proinflammatory cytokines, reduced the levels of proteins (e.g., phospho-IR, phospho-IRS-1 (Tyr612), phospho-AKT, and phospho-GSK-3α/β) involved in insulin signaling, and increased IRS-1 S307 phosphorylation compared to controls. Interestingly, visfatin increased the activities of the JAK2/STAT3 and IKK/NF-κB signaling pathways but not those of the JNK, p38, and ERK pathways. Visfatin-induced inflammation and insulin resistance were regulated by JAK2/STAT3 and IKK/NF-κB signaling; together with AG490 or Bay 7082, visfatin significantly reduced mRNA levels of IL-6, TNF-α and IL-1β and rescued insulin signaling. Conclusion. Visfatin induced proinflammatory cytokine production and inhibited insulin signaling via the STAT3 and NF-κB pathways in HepG2 cells.